2D and 3D Silica‐Template‐Derived MnO2 Electrocatalysts towards Enhanced Oxygen Evolution and Oxygen Reduction Activity. Issue 24 (26th October 2018) - Selvakumar, Karuppiah; Kumar, Sakkarapalayam Murugesan Senthil; Thangamuthu, Rangasamy; Rajput, Parasmani; Bhattacharyya, Dibyendu; Jha, Shambhu Nath
Abstract: In this work, a hard‐template‐based nano‐replication process is employed to prepare mesoporous MnO2 materials. We adopted four silica materials, namely, SBA‐15, KIT‐6, MCM‐41, and MCM‐48 as templates to prepare MnO2 materials by using a nanocasting route. The structural characteristics of the resultant MnO2 materials were thoroughly investigated by using XRD, BET, FESEM, HR‐TEM, XPS, and Raman techniques. All studies confirmed the replication of porous MnO2 nanostructures from silica supports in β‐crystallographic form. By employing X‐ray absorption near‐edge structure (XANES) and extended X‐ray absorption fine structure (EXAFS), we identified the existence of Mn and oxygen vacancies in the developed MnO2 material. The hydrodynamic linear sweep voltammetric technique was employed to demonstrate the efficient oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) activity of the catalyst in 0.1 M KOH solution. The KIT‐6‐derived MnO2 nanostructure displayed equal activity to the benchmark catalyst RuO2 . This work lays a foundation to prepare and employ ordered mesoporous MnO2 materials as OER/ORR catalysts, which have potential applications in electrochemical energy conversion and storage devices. Abstract : Bifunctional catalysts : Mesoporous MnO2 materials are obtained from a hard‐template‐based nanocasting method. SBA‐15, KIT‐6, MCM‐41, and MCM‐48 are selected as (2D and 3D) templates. The replication of porous MnO2 nanostructures from silica supports yields the β‐crystallographic form. X‐ray absorption studies identify the existence of Mn and oxygen vacancies in the materials. Electrochemical studies demonstrate efficient oxygen evolution and oxygen reduction reaction activity of the resultant materials. 3D MnO2 displays an activity comparable to the benchmark RuO2 catalyst.